An intensive dispersion and synchronous assembly of single-walled carbon nanotubes in a surfactant–oil–water association system. Issue 16 (4th April 2016) - Zhang, Yan; Li, Dechun; Wu, Lin; Zhou, Liang; Du, Yanan; Wang, Meng; Li, Ying
Abstract : An intensive dispersion and synchronous assembly of single-walled carbon nanotubes were achieved using a surfactant–oil–water association system. Abstract : This paper reports a novel approach for achieving an intensive dispersion and synchronous assembly of single-walled carbon nanotubes (SWNTs) using a surfactant–oil–water association system as medium. A kind of nonionic surfactant N, N -bis(2-hydroxyethyl)dodecanamide (DDA) which could form a bi-continuous network structure not only in water but also in dodecane was used. The SWNTs were infiltrated into the dodecane–DDA mixture instead of DDA aqueous solution, and the attractive van der Waals forces between the pristine SWNT agglomerates were decreased in the first place; the thorough dispersion of the SWNTs was completed in the subsequent phase transformation by adjusting the oil/water ratio, along with mild sonication stirring. The individual SWNTs with different chiralities, such as (6, 5), (7, 5), (7, 6), and (9, 4), are all separated well after mild centrifugation treatment, which was confirmed by the well-resolved UV-Vis-NIR absorption and sharp fluorescence spectra. In particular, the self-assembly of DDA drove the separated individual SWNTs forming a large scale spatial network architecture. We believe that the SOW–SWNT suspension has high potential in constructing new functional materials by introducing diverse desirable components through the oil phase and also the water phase medium.